The impact of privacy authorization framing in mobile apps on privacy disclosure: a regulatory focus approach - Zhuo Sun; Dandan Zhang; Xiaoning Gao; Yan Jin (Information Research: An International Electronic Journal)
Purpose. In the digital age, the tension between mobile app users obtaining personalized services and granting privacy permissions has become increasingly pronounced. The behavioral drivers and mechanisms influencing privacy disclosure in the context of privacy permissions require further investigation. By focusing on users' privacy disclosure intentions, this study aims to assist app platforms in designing privacy permission content that aligns with consumers' diverse privacy preferences and psychological needs, providing theoretical guidance and references for efficient platform operation.